Perancangan Aplikasi Mobile untuk Rekomendasi Kuliner Lokal - Efrans Michael Harahap; Jamaluddin Jamaluddin; Eva Julia Gunawati Harianja; Marlyna Infryanty Hutapea; Resianta Parangin-angin (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2026)
The rapid advancement of information technology has shifted the paradigm of tourism and culinary exploration towards mobile platforms. However, local culinary searches in Medan City are currently still conventional and random. Scattered culinary information across various social media without a comprehensive summary often confuses customers and complicates the promotion of micro-culinary businesses (UMKM) in the digital era. Existing commercial platforms often burden local sellers with high platform taxes. This research aims to design and implement an Android-Based Mobile Application for Local Culinary Recommendations as an effective solution to these problems. This application is built natively using the Java programming language for the Android client side, integrated with a PHP Application Programming Interface (API) and MySQL relational database. The system design involves a Client-Server architecture and includes three distinct access rights: User, Culinary Admin, and Super Admin. Implemented features include dining place search, interactive reviews, ratings, popularity levels based on view counts, and Google Maps API integration for precise culinary navigation routes. The result of this research is a self-managed mobile application that accelerates navigation access for users while assisting business owners in managing their stalls independently, objectively, and expanding their promotional reach without internal transaction fees.